PESAN PROFETIK CERPEN BERTEMA ‘AMPLOP KIAI’, SEBUAH KAJIAN SOSIOLOGIS DAN IMPLEMENTASINYA DALAM PEMBELAJARAN SASTRA DI SEKOLAH - Muhajir Muhajir; Ika Septiana; Ahmad Ripai (Teks: Jurnal Penelitian Bahasa, Sastra, dan Pengajarannya, 2023)
AbstractThis study took four short stories as material objects, namely "Amplop susulan" by Teguh Effendi, (Effendi, 2017) "Kiai Amplop" written by Edy Yuswanto, (Yuswantoro, 2011) "Amplop ustadz manfaat" is a short story by Effendi Thahar, (Thahar, 2016) "Amplop-Amplop Abu-Abu" written by a kiai named "A. Mustofa Bisri" (Bisri, 2017).  The research method used in this research is qualitative method. The stages carried out are research and take noted  and then describing. The purpose of the research is to find the perception or response of the kiai or ustadz to the envelope he received, to find prophetic messages in the short stories studied, and their implementation in learning literature at school.